Bronchodilatory, antitussive and anti-inflammatory effect of morin in the setting of experimentally induced allergic asthma. (10th June 2016) - Franova, Sona; Kazimierova, Ivana; Pappova, Lenka; Joskova, Marta; Plank, Lukas; Sutovska, Martina
Abstract: Objective: Using an experimental model of allergic asthma, we evaluated the anti-asthmatic potential of polyphenol flavonol derivate morin after either acute or long-term treatment of male OVA-sensitised guinea pigs. Methods: The following methods were used in experiments: the in-vitro tracheal smooth muscle contraction induced by histamine; the changes in specific airway resistance (sRaw) to histamine and the sensitivity of a chemically induced cough reflex both via an in-vivo method; the serum and BALF concentrations' analysis of the inflammatory cytokines interleukin IL-4, IL-5, IL-13; and lung tissue infiltration by eosinophils and mastocytes. Key findings: Our data show that acute morin (30 mg/kg) and chronic 21-day morin (30 mg/kg/day) administration had a comparable antitussive efficiency with opioid antitussive codeine. Acute morin bronchodilatory activity defined by in-vivo sRaw decline did not reach SABA salbutamol effect. However, bronchodilatory efficiency of morin after long-term administration was by 34% higher as effect of LABA salmeterol. The 21-day morin treatment of OVA-sensitised guinea pigs reduced the serum, BALF levels of IL-4 and IL-13, lung tissue eosinophil and mastocyte infiltration comparable with corticosteroid budesonide. Conclusions: In summary, morin represents very rational target for additional studies as potential substance for control as well as prevention of asthma inflammation and symptoms.